Mid‐Holocene vegetation dynamics in the Tejo River estuary based on palaeobotanical records from Ponta da Passadeira (Barreiro–Setúbal, Portugal). (13th February 2014) - Gómez‐Orellana, Luis; Ramil‐Rego, Pablo; Badal, Ernestina; Carrión Marco, Yolanda; Muñoz Sobrino, Castor
<x xml:space="preserve">Abstract</x> This paper presents the results of pollen and charcoal analyses carried out in the sedimentary formation of Ponta da Passadeira, south of the Tejo River estuary, Portugal. The data provide information regarding the evolution of the coastline and ecosystem of the estuary during the mid and late Holocene. The study focuses on a group of upright woody fossilized tree remains that, together with those identified earlier by García‐Amorena et al. (2007), form part of the fossil forest of Ponta da Passadeira. Eight remains were identified as Pinus pinaster, four as Pinus pinea and one as Pinus sp. Two specimens of these species were dated to 6523 and 5805 cal. a BP. Pollen analysis was undertaken in a clay layer located at the same point as the fossil forest, which is currently below sea level; the base of the clay layer was dated to 4906 cal. a BP. The pollen spectra reflect the dynamics of the vegetation that grew on this deposit, whereas the sporopollinic input masks the contribution of the regional vegetation. Wood charcoal remains recovered at an adjacent Final Neolithic settlement were also analysed, and a Pinus sp. specimen was radiocarbon dated to 5050 cal. a BP. The correlation amongst the three records provides key ecological markers for the understanding of the evolution of coastline ecosystems, and helps to clarify and understand the Holocene sea rise on the Atlantic seaboard of Iberia. The geographical location of Ponta da Passadeira is strategic because it enables a more clear definition of the configuration of landscapes that show an inflection point in this area of central Portugal.